2010
DOI: 10.1128/jcm.01101-10
|View full text |Cite
|
Sign up to set email alerts
|

Normalized Resistance Interpretation as a Tool for Establishing Epidemiological MIC Susceptibility Breakpoints

Abstract: Normalized resistance interpretation (NRI) utilizes the fact that the wild-type population on the sensitive side is not affected by resistance development, and therefore a normalized reconstruction of the peak can be performed Traditional concepts for setting interpretive breakpoints in antimicrobial susceptibility testing were challenged by J. D. Williams in 1990 when he proposed the setting of so-called microbiological guidelines in relation to the distribution of inhibition zone diameter values (or MIC valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
75
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 24 publications
2
75
1
Order By: Relevance
“…The results obtained, in general, were the same as those found with all 2,119 isolates or fell within one 2-fold dilution, which is in agreement with the work of Turnidge et al and Kronvall, who reported that their methods are also valid for data sets generated by a single laboratory and method (12,27). It is difficult to determine which statistical method defines the ECV best, due to the scarcity of resistant isolates.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The results obtained, in general, were the same as those found with all 2,119 isolates or fell within one 2-fold dilution, which is in agreement with the work of Turnidge et al and Kronvall, who reported that their methods are also valid for data sets generated by a single laboratory and method (12,27). It is difficult to determine which statistical method defines the ECV best, due to the scarcity of resistant isolates.…”
Section: Resultssupporting
confidence: 77%
“…Since the ECVs estimated by the clustering method are on a continuous scale, values were rounded to the nearest higher dilution after reconversion to concentration units. 50 or modal MIC (6,12,27). We used the clustering statistical method to determine ECVs and compared them with those obtained by other methods and with those reported for the CLSI methodology.…”
Section: Fig 1 Example Of a Normal Mixture Distribution (A) And Distrmentioning
confidence: 99%
See 1 more Smart Citation
“…With the intermediate MIC values of the Etest, enough data points were obtained for successful mathematical calculations [65]. Also, regular 2-log dilution MIC distributions have now been analysed using NRI, made possible by the introduction of helper variables [66]. With such objective methods also applied to MIC distributions and the advent of pharmacokinetic/pharmacodynamic-Monte Carlo simulations for defining MIC epidemiological breakpoints, it seems that this changing pattern has come full circle.…”
Section: Page 16 Of 38mentioning
confidence: 99%
“…To date, several methods have been proposed to determine inhibition zone diameter cutoffs, such as the error rate-bounded method (7), a modified error rate-bounded method (8), the normalized resistance interpretation method (9,10), and few statistical inference approaches (11,12). However, visual inspection of distributions (eyeball method) has usually been applied to determine cutoffs (12)(13)(14)(15)(16).…”
mentioning
confidence: 99%